Interaction of the Excited Electronic States of Carbon Quantum Dots and Molecular Oxygen - Ibrayev, N. Kh.; Seliverstova, E.V. (Eurasian Journal of Chemistry, 2023)
The S,N-doped carbon quantum dots based on citric acid and L-cysteine were synthesized. The sizes of the synthesized carbon dots vary from 4 to 10 nm. The absorption spectrum exhibits a band with a maximum at 360 nm, as well as a shoulder at about 240–250 nm. The fluorescence band of the studied carbon dots is located in the region of 370–600 nm with a maximum at ~430 nm. The properties of the long-lived luminescence of carbon quantum dots solutions were studied. It was established that the decay of triplet states occurs as a result of a radiative phosphorescent transition and triplet–triplet annihilation. The synthesized carbon quantum dots are reviled to be the singlet oxygen sensitizers, as evidenced by the observed luminescence of molecular oxygen upon excitation of solutions in the absorption band of the carbon quantum dots. It was shown that when O2 3( )g −  was added to the solution, the process of singlet–triplet annihilation develops, the efficiency of which depends on the concentrations ratio of triplet carbon quantum dots and singlet O2(1Δg) molecules. In the presence of plasmonic Ag nanoparticles, the phosphorescence of singlet oxygen is enhanced.
Keywords: carbon quantum dots; singlet oxygen; excited states; delayed fluorescence; phosphorescence; Ag nanoparticles; plasmons